Effect of soil-moisture regime on plant growth, fruiting, fruit quality and nutrient uptake of mango (Mangifera indica) - SINGH, RANBIR; CHANDEL, J S; BHANDARI, A R (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1990-.92 to study the effect of soil-moisture regimes on plant growth, fruiting, fiuit quality and mineral composition and to work out the irrigation water requirement for bearing mango (Mangifera indica L.) trees. Plant height, shoot growth, fruit retention, fruit quality, yield and leaf nutrient status were fOund significantly higher in trees irrigated at 20 and 40% depletion of available soil-moisture than those irrigated at 60% depletion of available soil-moisture and unirrigated control. There was 87 and 79% increase in yield when irrigation was applied at 20 and 40% depletion of available soil-moisture, respectively compared with the unirrigated control. Though the plant growth, yield and fruit quality were slightly better in trees irrigated at 20% depletion of available soil-moisture than those irrigated at 40% depletion of available soil-moisture but there was 8.07% saving of water in 40% irrigation treatment without any adverse effect on tree growth, yield and fruit quality as observed in trees irrigated at 60% depletion of available soil-moisture and unirrigated control. Trees required 21-23 irrigations amounting to 125.4 cm of irrigation water/year at 40% available soil-moisture depletion level.